2008
DOI: 10.1176/appi.ap.32.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Stigma: Involving Families in Medical Student and Psychiatric Residency Education

Abstract: The educational collaborations between advocacy groups and academia show promise for increasing communication about psychiatric disorders, treatment, and stigma issues between families and psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 6 publications
0
25
0
1
Order By: Relevance
“…Comparisons of the studies are shown in Table 1. In 21 studies, the participants were university or college students, including those studying medicine, nursing and psychology 17–37 and 18 studies included children or adolescents aged younger than 18 in schools 38–55 . One study included both school students (under 18) and college students 55 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons of the studies are shown in Table 1. In 21 studies, the participants were university or college students, including those studying medicine, nursing and psychology 17–37 and 18 studies included children or adolescents aged younger than 18 in schools 38–55 . One study included both school students (under 18) and college students 55 …”
Section: Resultsmentioning
confidence: 99%
“…Nine studies used a control group or comparison group that were provided different types of educational intervention (clinical controlled trial) 19,30–32,40–44 . Other studies were contacted pre‐ and post‐test to assess young people's stigmatization without control or comparison groups (pre/post study) 33–37,45–55 . In addition, there were 14 studies that conducted long‐term follow ups 16–18,20,31,37,38,42,43,45,48–50,55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Among medical students, initiatives involving brief presentations, elective experiences, and month-long courses have included a combination of education, testimonials, social/patient contact, case-based discussion, and role playing, with positive pre/post outcomes often noted but longer-term gains less supported. [69][70][71][72][73][74] It appears that the timing and selection of instruction may influence medical student receptivity to learning about depression and its treatment, 75 which suggests that consideration be given to contextappropriate and culturally relevant placement of stigma reduction programming within the curriculum. 76 Limitations This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the papers presented here argue rigorously and compellingly about the need to study psychiatric ethics topics in new areas and in greater depth. Examples include the impact of the therapeutic misconception; the effectiveness of institutional review boards and other research safeguards; the connections between innovative clinical practice, access to clinical care for underserved populations, and clinical research; the special issues for psychiatric research involving children, elders, and individuals with co-occurring disease; the uptake and influence of innovative tools and approaches in medicine that have not yet been clinically validated; the role of cultural ethics; and the effects of stigma in clinical care, public policy, and health services for people with mental illness, among many other areas (Feldman 2005;Larson and Corrigan 2008;Layde 2004;Lu and Primm 2006;Roberts 2010;Schmetzer and LaFuze 2008;Tsao et al 2008). The priority assigned to topics should honor not only our interests as thought leaders and investigators but also the interests of the diverse stakeholders of relevance to neuropsychiatric disease.…”
mentioning
confidence: 99%